Tyrosine Kinase Inhibitor-Induced Hypertension: Role of Hypertension as a Biomarker in Cancer Treatment - Budolfsen, Cecilie; Faber, Julie; Grimm, Daniela; Krüger, Marcus; Bauer, Johann; Wehland, Markus; Infanger, Manfred; Magnusson, Nils E. (Current Vascular Pharmacology, 2019)
Cancer treatment is an area of continuous improvement. Therapy is becoming more targeted and the use of anti-angiogenic agents in multiple cancers, specifically tyrosine kinase inhibitors (TKIs), has demonstrated prolonged survival outcomes compared with previous drugs. Therefore, they have become a well-established part of the treatment. Despite good results, there is a broad range of moderate to severe adverse effects associated with treatment. Hypertension (HTN) is one of the most frequent adverse effects and has been associated with favourable outcomes (in terms of cancer treatment) of TKI treatment. High blood pressure is considered a class effect of TKI treatment, although the mechanisms have not been fully described. Three current hypotheses of TKI-associated HTN are highlighted in this narrative review. These include nitric oxide decrease, a change in endothelin-1 levels and capillary rarefaction. Several studies have investigated HTN as a potential biomarker of TKI efficacy. HTN is easy to measure and adding this factor to prognostic models has been shown to improve specificity. HTN may become a potential biomarker in clinical practice involving treating advanced cancers. However, data are currently limited by the number of studies and knowledge of the mechanism of action.
Keywords: sorafenib